1 tìm số nguyên y,biết a)(y+6)^2=(-10)^2-6^2 b)(y-6)^2=(-8)^2 c)(6-y)^2=81 d)(y+3)^3=-125 e)(y-4).(y+20)=0

1 tìm số nguyên y,biết
a)(y+6)^2=(-10)^2-6^2
b)(y-6)^2=(-8)^2
c)(6-y)^2=81
d)(y+3)^3=-125
e)(y-4).(y+20)=0

1 bình luận về “1 tìm số nguyên y,biết a)(y+6)^2=(-10)^2-6^2 b)(y-6)^2=(-8)^2 c)(6-y)^2=81 d)(y+3)^3=-125 e)(y-4).(y+20)=0”

  1. a) (y+6)^2=(-10)^2-6^2
    (y+6)^2=100-36=64
    TH1:
    (y+6)^2=8^2
    y+6=8
    y=2
    TH2:
    (y+6)^2=(-8)^2
    y+6=-8
    y=-14
    b)(y-6)^2=(-8)^2
    y-6=-8
    y=2
    c)(6-y)^2=81
    TH1:
    (6-y)^2=(-9)^2
    6-y=-9
    y=15
    TH2:
    (6-y)^2=9^2
    6-y=9
    y=-3
    d)(y+3)^3=-125
    (y+3)^3=(-5)^3
    y+3=-5
    y=-8
    e)(y-4)(y+20)=0
    TH1:
    y-4=0
    y=4
    TH2:
    y+20=0
    y=-20
    => x=-4;20

    Trả lời

Viết một bình luận

Câu hỏi mới